(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This study used Geometry Interactive software (GIS) to ascertain students’ geometry achievement at senior secondary school one (SS1). Quasi-experimental design of non-randomized pre-test post-test control group design was utilized. The research was carried out in Wukari Local Government Area of Taraba State with a population of 1,003 senior secondary one students. From this, 68 students were sampled from two schools out of nine governments owned senior secondary schools. The research instrument was Geometry Achievement Test (GAT). The reliability of the instruments was 0.85. Four research questions were asked and answered with means and standard deviations while the four hypotheses formulated were tested using Analysis of Covariance (ANCOVA) at 0.05 level of significance. The study found among others that students taught using Geometry Interactive Software (GIS) improved in their achievement in geometry more than those taught geometry using conventional strategy. Recommendations such as incorporating Interactive Software (IS) among instructional strategies for teaching mathematical concepts as well as encouraging Proprietors of schools to purchase interactive software for their students in the schools were made among others.